Innate IFN-γ-Producing Cells in the Spleen of Mice Early after Listeria monocytogenes Infection: Importance of Microenvironment of the Cells Involved in the Production of Innate IFN-γ - Kubota, Koichi; Kadoya, Yuichi (Frontiers in Immunology, 2011)
Production of innate interferon-gamma(IFN-gamma) is a crucial step in immunological defense against bacteria. However, there is little information regarding cellular mechanisms underlying IFN-gamma production in vivo early after bacterial infection. Here we analyze innate-IFN-gamma production in the spleen of mice early after Listeria monocytogenes (LM) infection ex vivo by flow-cytometry and in situ by immunohistochemisrty, and compare them with the IFN-gamma-producing cells reported previously in our in vitro coculture system in which cell-cell interaction between lymphocytes and dying bacterial-infected macrophages is required for the production of IFN-gamma. In the spleen at 20 h after LM infection, natural killer (NK) cells, a subset of alpha/beta T cells, and subsets of NKT and gamma/delta T cells produced IFN-gamma with features similar to the IFN-gamma-producing cells in our in vitro coculture system. Immunohistochemistry revealed that LM bacteria were first phagocytosed mainly by ER-TR9+ marginal-zone macrophages (MZMs), then forming infectious foci in close vicinity of the marginal zone (MZ) at 20-h postinfection. At this time point, the IFN-gamma-producing cells were accumulating at the same site of infectious foci, around which ER-TR9+ MZMs were clustered but most of bacteria were no longer associated with ER-TR9+ MZMs. These results indicate that innate-IFN-gamma production by innate lymphocytes takes place at infectious foci formed in close vicinity of the MZ, and they also suggest an important role for the microenvironment of the cells accumulated at infectious foci in inducing the production of innate IFN-gamma.